The Influence of Learning Model Self Directed Learning and Personality on Student Learning Results of SMP Negeri 7 Kota Ternate - Irfan Ilyas; Agung Purwanto; Uswatun Hasanah (International Journal of Education, Information Technology, and Others, 2020)
The purpose of this study was to determine the effect oflearning models Self directed learning (SDL) and Personality on student learning outcomes in the structure and function of plant tissue. This study uses an experimental method of 2 x 2 factorial design with a sample of 60 Grade VII students of SMPN-7 Ternate City. The results showed that (1) There was a significant difference in learning outcomes between students learning with thelearning model Self directed learning and students learning to use thelearning model conventional. with an average score of learning outcomes (A1) is 75.75, and (A2) is 71.25; (2) There is an effect of interaction between learning models and personality on learning outcomes (AXB) is 78.6% (R. Squared = 0.786); (3) There is a significant difference in student learning outcomes with Extrovert Personality, having better learning outcomes when using themodel Self directed learning. The score of student learning outcomes (A1B1) is 83.00 while (A2B1) is 66.75 and theTest Tuckey average score of 24.33; (4) There is a significant difference between students' learning outcomes and Self directed learning andlearning models Conventional for students with Personality Introvert (A2B2) is 75.75 and theTest has Tuckey an average score of 7.25. In conclusion, thelearning model Self directed learning can improve student learning outcomes in the material structure and function of plant tissues by considering the extroverted and introverted personality types of students.